Discrete Compositional Representations as an Abstraction for Goal Conditioned Reinforcement Learning - Islam, Riashat; Zang, Hongyu; Goyal, Anirudh; Lamb, Alex; Kawaguchi, Kenji; Liu, Xin; Laroche, Romain; Bengio, Yoshua; Tachet des Combes, Remi (2022)
Abstract to come...